Molecular fishing: marine oligosaccharides - Trincone, Antonio (Frontiers in Marine Science, 2014)
It is difficult to overvalue the importance of polysaccharides for the great number of applicative fields in which they appeared. Oligosaccharides are relatively short compounds that are prepared from the longer polysaccharides or could also be found as such in nature. The potential in bioactivity of marine polysaccharides is still considered under-exploited and these molecules, including the derived oligosaccharides, are an extraordinary source of chemical diversity. Sustainable ways to access marine oligosaccharides are particularly important in view of the huge list of the effects they play in cell events; enzymatic tools, on which these sustainable ways are based, and modern techniques for purification and for the investigation of chemical structures, will be shortly discussed indicating the most important recent literature.